Hemodynamic Signal Changes Accompanying Execution and Imagery of Swallowing in Patients with Dysphagia: A Multiple Single-Case Near-Infrared Spectroscopy Study - Kober, Silvia Erika; Bauernfeind, Günther; Woller, Carina; Sampl, Magdalena; Grieshofer, Peter; Neuper, Christa; Wood, Guilherme (Frontiers in Neurology, 2015)
In the present multiple case study, we examined hemodynamic changes in the brain in response to motor execution (ME) and motor imagery (MI) of swallowing in dysphagia patients compared to healthy matched controls using near-infrared spectroscopy (NIRS). Two stroke patients with cerebral lesions in the right hemisphere, two stroke patients with lesions in the brainstem, and two neurologically healthy control subjects actively swallowed saliva (ME) and mentally imagined to swallow saliva (MI) in a randomized order while changes in concentration of oxygenated hemoglobin (oxy-Hb) and deoxygenated hemoglobin (deoxy-Hb) were assessed. In line with recent findings in healthy young adults, MI and ME of swallowing led to the strongest NIRS signal change in the inferior frontal gyrus in stroke patients as well as in healthy elderly. We found differences in the topographical distribution and time course of the hemodynamic response in dependence on lesion location. Dysphagia patients with lesions in the brainstem showed bilateral hemodynamic signal changes in the inferior frontal gyrus during active swallowing comparable to healthy controls. In contrast, dysphagia patients with cerebral lesions in the right hemisphere showed more unilateral activation patterns during swallowing. Furthermore, patients with cerebral lesions showed a prolonged time course of the hemodynamic response during MI and ME of swallowing compared to healthy controls and patients with brainstem lesions. Brain activation patterns associated with ME and MI of swallowing were largely comparable, especially for changes in deoxy-Hb. Hence, the present results provide new evidence regarding timing and topographical distribution of the hemodynamic response during ME and MI of swallowing in dysphagia patients and may have practical impact on future dysphagia treatment.